From the nonrelativistic Morse potential to a unified treatment of a large class of bound‐state solutions of a modified D‐dimensional Klein–Gordon equation. Issue 9 (26th December 2017) - Garcia, M. G.; de Castro, A. S.; Castro, L. B.; Alberto, P.
Abstract : Bound‐state solutions of the D ‐dimensional Klein–Gordon equation for a large set of couplings and potential functions are generated from the nonrelativistic bound‐state solutions of the one‐dimensional generalized Morse potential. Added bonuses from these mappings are the straightforward determination of the critical attractive singular potential and the proper boundary condition on the radial eigenfunction at the origin.